Convenient method of producing cyclic single-chain Fv antibodies by split-intein-mediated protein ligation and chaperone co-expression. (10th April 2020) - Liu, Chenjiang; Kobashigawa, Yoshihiro; Yamauchi, Soichiro; Fukuda, Natsuki; Sato, Takashi; Masuda, Takeshi; Ohtsuki, Sumio; Morioka, Hiroshi
Abstract: Single-chain Fv (scFv) is a recombinant antibody in which the variable regions of the heavy chain (VH) and light chain (VL) are connected by a short flexible polypeptide linker. Compared with monoclonal antibodies, scFvs have the advantages of low-cost production using Escherichia coli and easy genetic manipulation. ScFvs are, therefore, regarded as useful modules for producing next-generation medical antibodies. The practical use of scFvs has been limited due to their aggregation propensity mediated by interchain VH–VL interactions. To overcome this problem, we recently reported a cyclic scFv whose N-terminus and C-terminus were connected by sortase A-mediated ligation. Preparation of cyclic scFv is, however, a time-consuming process. To accelerate the application study of cyclic scFv, we developed a method to produce cyclic scFv by the combined use of a protein ligation technique based on protein trans -splicing reaction (PTS) by split intein and a chaperone co-expression system. This method allows for the preparation of active cyclic scFv from the cytoplasm of E. coli. The present method was applied to the production of cyclic 73MuL9-scFv, a GA-pyridine antibody, as a kind of advanced glycation end-product. These findings are expected to evoke further application study of cyclic scFv.